O currículo de um curso de licenciatura em Educação Física pós-diretrizes curriculares: da prescrição ao cotidiano da formação - Alves, Cláudia Aleixo (2019)
The present study is the result of a dissatisfaction with the way in which studies on the field of training and curriculum in Physical Education have dealt with the National Curricular Guidelines (DCNs) for higher education, in particular Resolutions CNE/CP 01/2002; CNE/CP 02/2002; CNE/CES 07/2004 and CNE/CP 02/2015, which, among other aspects, started to define different training paths for Teacher Training and Bachelor degrees. In view of the positions related to the current DCNs, it is noticed that the studies sometimes present a conception of curriculum as a document that only complies with the law as if it could not be interpreted. It is not known, however, that curricula are carried out in daily life according to criteria established by them and not limited to these guidelines. In addition, it is understood that the debate around the DCNs has ignored the fact that the curricula are realized also in the quotidian of the formation. Therefore, the objective of this investigation is to know the repercussions of the DCNs in the dynamic process that involves (re)interpretation, (re)appropriation and (re)invention of the curricular document in the daily life of a degree in physical education, of an Institution of Higher Education. In order to understand the repercussions of the DCNs in three instances: in the formative and professional projects of the students, since the students would have to choose the degree or the baccalaureate before entering the course; in the valuation of the knowledge in the curriculum, in order to verify if the DCNs were able to change the scientific tradition of the physical education in the curriculum of the institution investigated; and, finally, in the identity of the degree, in order to know if the training of teachers was configured as the central objective of the course. For that, an ethnographic study was conducted, with a one-year follow-up of the curricular routine of the School of Physical Education, Physiotherapy and Occupational Therapy (EEFFTO) of the Federal University of Minas Gerais. The thesis is that the DCNs occupy a secondary place in the way the curricula are carried out in the daily life of the formation, since the modes like EEFFTO, the teachers and the students conceive the Physical Education as academic, scientific area, of professional formation, and also as a curricular component, end up having greater repercussions in the process that involves the mediation between the prescribed curriculum and the lived curriculum. The results reinforce the thesis in identifying that the DCNs, although they had provided legal conditions for the creation of a curricular proposal that was aligned with the identity of the Degree, which in fact was successful, could not, within the curriculum lived, delimit this identity, since there is no consensus about this identity between students and teachers. It was found that the DCNs did not manage to substantially alter the training and professional projects of the students who entered the course, nor did they break with their criteria for valuing their knowledge. In the latter case, it was found that aspects unrelated to DCNs such as hierarchization and the way knowledge is treated in the educational process, as well as the relation of knowledge to professional practice, had a greater influence on the students' evaluation criteria of the disciplines. Finally, the study potentiated the notion of curriculum as a social construction, marked by conflicts arising from the different ways of conceiving Physical Education both epistemologically and politically.